A design framework for exploratory geovisualization in epidemiology - Robinson, Anthony C. (2007)
This paper presents a design framework for geographic visualization based on iterative evaluations of a toolkit designed to support cancer epidemiology. The Exploratory Spatio-Temporal Analysis Toolkit (ESTAT), is intended to support visual exploration through multivariate health data. Its purpose is to provide epidemiologists with the ability to generate new hypotheses or further refine those they may already have. Through an iterative user-centered design process, ESTAT has been evaluated by epidemiologists at the National Cancer Institute (NCI). Results of these evaluations are discussed, and a design framework based on evaluation evidence is presented. The framework provides specific recommendations and considerations for the design and development of a geovisualization toolkit for epidemiology. Its basic structure provides a model for future design and evaluation efforts in information visualization.